The Use of Wondershare Quiz Creator Evaluation Media to Improve Student Learning Outcomes in Citizenship Education Courses - Khoirunnisak, Anis; Kuncorowati, Puji Wulandari; Marzuki, Marzuki (Jurnal Pendidikan Indonesia, 2022)
Evaluation of learning in Citizenship Education courses must be developed in a variety of ways with online-based learning evaluations so that students can improve learning outcomes. Conventional evaluation methods can affect student learning outcomes, so educators must always innovate in learning activities. This study aims to determine the use of online-based Wondershare Quiz Creator evaluation media that can increase the average value of Citizenship Education courses for S1 Catering students at Yogyakarta State University. This study used an experimental method consisting of two groups, namely the Pre-test and Post-test groups. The sample was selected using cluster random sampling technique and multiple-choice test with a total of 20 questions. Data analysis shows that there is a significant difference between the results of the Pre-test and Post-test t, the average value of the Post-test t is 79.50 which is higher than the average value of the Pre-test of the experimental group is 69.30. The results of the research in the field prove that there is an effect of using conventional evaluation methods with online-based evaluations with online-based Wondershare Quiz Creator evaluation media which is known from the results of students' pre-test and Post-test scores on the evaluation of the Citizenship Education course.